Improving freeze-thaw stability of soy nanoparticle-stabilized emulsions through increasing particle size and surface hydrophobicity. (February 2019) - Chen, Ye-Bao; Zhu, Xue-Feng; Liu, Tong-Xun; Lin, Wei-Feng; Tang, Chuan-He; Liu, Ruihai
Abstract: There is increasing interest in improving the freeze-thaw stability of emulsions by interfacial engineering in the food colloid field. The present work reported that for Pickering emulsions stabilized by heat-induced soy protein isolate (SPI) nanoparticles, their freeze-thaw stability could be well modulated by modifying the characteristics of the nanoparticles. The SPI nanoparticles with different characteristics (e.g., particle size, surface hydrophobicity) were obtained by heating the SPI solutions at initial concentrations ( c i ) of 0.25–6.0 wt% at 95 °C for 15 min. All the initial Pickering emulsions were formed at an oil fraction of 0.4 and protein concentration of 0.25 wt% in the aqueous phase, in the presence of 300 mM NaCl. In general, increasing the c i resulted in a progressive enhancement in freeze-thaw stability of the emulsions against creaming and coalescence, but accelerated the flocculation. The higher creaming stability at higher c i values seemed to be closely associated with the enhanced coalescence stability, as well as the strengthened gel-like network of these initial emulsions. There were close interplays between the freeze-thaw stability and the properties of the initial emulsions, or characteristics (e.g. particle size or surface hydrophobicity) of heat-induced SPI nanoparticles. The results confirmed that the SPI nanoparticles with larger sizes, higher surface hydrophobicity and more efficient packing at interface exhibit a greater potential to produce Pickering emulsions with higher freeze-thaw stability. The findings would be of relevance for understanding the freeze-thaw stability of Pickering emulsions stabilized by protein-based particles, as well as for the development of protein-stabilized emulsion formulations with a high freeze-thaw stability. Graphical abstract: Image Highlights: Different SPI nanoparticles were fabricated by heating SPI solutions at different concentrations ( c i ). Increasing the c i resulted in a gradual increase in particle size and surface hydrophobicity. The freeze-thaw stability of the emulsions against creaming and coalescence inreased with the c i . Close relationships between the particle characteristics and freeze-thaw stability of the emulsions were observed. The gel-like network formation also contributed to the freeze-thaw stability.